DIGITAL TRANSFORMATION IN PUBLIC SERVICES: LESSONS FROM THE INVESTMENT AND INTEGRATED ONE-STOP SERVICES OFFICE OF BIMA REGENCY - Arman; Mas’ud; Syamsuddin (KOMUNITAS, 2024)
This research examines challenges in digitizing public services, particularly licensing, in Bima District, emphasizing its impact on community well-being and the local economy. Through qualitative methods such as literature review, interviews, and observation, it identifies hurdles like low digital literacy and inadequate infrastructure. Despite progress, challenges persist. Yet, system integration and increased investment yield positive results, enhancing service efficiency and investment attraction. Further efforts are required to improve infrastructure and IT training for greater digital transformation. Collaboration among government, community, and private sector is crucial for success, supporting local economic growth and community engagement in public services. This study provides insights for informed decision-making and sustainable policy development, contributing to the advancement of digital transformation in Bima District.